Barriers to the uptake of solar-powered irrigation by smallholder farmers in Sub-Saharan Africa: A review - Durga, Neha; Schmitter, Petra S.; Ringler, Claudia; Mishra, Shrishti; Magombeyi, Manuel Simba; Ofosu, Abena; Pavelic, Paul; Hagos, Fitsum; Melaku, Dagmawi; Verma, Shilp; Minh, Thai Thi; Matambo, Chamunorwa (Elsevier, 2024)
Irrigation expansion is critical for agricultural and rural development, food and nutrition security, and climate change adaptation in Sub-Saharan Africa (SSA). Lack of accessible energy for irrigation development due to limited off- and on-grid infrastructure and the resulting dependence on costly fuel-based irrigation have been key inhibiting factors for irrigation expansion in the region. Off-grid solar-powered irrigation pumps (SIPs) can overcome many of the energy access and other challenges in the region, but their uptake has been slow. Given the nascent development of the solar irrigation sector in SSA, this paper combines a review of the peer-reviewed and grey literature with key informant interviews to identify systemic barriers to the adoption and growth of solar-powered irrigation. We identify uncovered risks, lack of incentives, and lack of capacity as the key factors limiting the adoption of solar-powered irrigation. Moreover, despite significant global cost reductions, solar-powered irrigation systems remain costly in SSA due to limited market development and geographical constraints. Lack of regulation and low investment in building local institutions and value chains further affect uptake and inhibit leveraging the energy transition for ensuring food security and agriculture-led poverty alleviation in SSA. We propose a move away from thinking of SIPs as “silver bullets” and towards a systems approach and the design of context-specific solutions to address risks, incentives and capacity challenges.